Aptamer/AuNP Biosensor for Colorimetric Profiling of Exosomal Proteins. Issue 39 (21st August 2017) - Jiang, Ying; Shi, Muling; Liu, Yuan; Wan, Shuo; Cui, Cheng; Zhang, Liqin; Tan, Weihong
Abstract: Exosomes constitute an emerging biomarker for cancer diagnosis because they carry multiple proteins that reflect the origins of parent cells. Assessing exosome surface proteins provides a powerful means of identifying a combination of biomarkers for cancer diagnosis. We report a sensor platform that profiles exosome surface proteins in minutes by the naked eye. The sensor consists of a gold nanoparticle (AuNP) complexed with a panel of aptamers. The complexation of aptamers with AuNPs protects the nanoparticles from aggregating in a high‐salt solution. In the presence of exosomes, the non‐specific and weaker binding between aptamers and the AuNP is broken, and the specific and stronger binding between exosome surface protein and the aptamer displaces aptamers from the AuNP surface and results in AuNP aggregation. This aggregation results in a color change and generates patterns for the identification of multiple proteins on the exosome surface. Abstract : A coat of many colors : A gold nanoparticle/aptamer biosensor (AuNP/Apt X ) provides a colorimetric platform for rapid and multiplexed protein analysis of exosomes.